Bluetooth for Internet of Things: A fuzzy approach to improve power management in smart homes. (May 2015) - Collotta, M.; Pau, G.
Graphical abstract: Abstract: Thanks to the introduction of the Internet of Things (IoT), the research and the implementation of home automation are getting more popular because the IoT holds promise for making homes smarter through wireless technologies. There is a main requirement that make a wireless protocol ideal for use in the IoT, that is the energy efficiency. Bluetooth Low Energy (BLE) has a high potential in becoming an important technology for the IoT in low power, low cost, small devices. However, specific techniques can be used in such a way as to further reduce the energy consumption of BLE. To this end, this paper proposes a fuzzy logic based mechanism that determine the sleeping time of field devices in a home automation environment based on BLE. The proposed FLC determines the sleeping time of field devices according to the battery level and to the ratio of Throughput to Workload (Th/Wl). Simulation results reveal that using the proposed approach the device lifetime is increased by 30% with respect to the use of fixed sleeping time.